Analysing event data from a repairable machine subject to imperfect preventive maintenance - Jack, N. (Quality and reliability engineering international, 1997)
A machine is minimally repaired on failure and imperfect preventive maintenance (PM) is also carried out from time to time, not necessarily at regular intervals. A simple point process model is proposed for the sequence of corresponding failure times, and estimates of the machine lifetime parameters and the degree of age rejuvenation at PMs are obtained using maximum likelihood techniques. These results are then applied to real event data. © 1997 John Wiley & Sons, Ltd.